Chlorogenic and 1,5-Dicaffeoylquinic acid-rich extract of topinambur (Helianthus tuberosus L.) exhibits strong antioxidant activity and weak cytotoxicity - Sharopov, Farukh; Wetterauer, Bernhard; Gulmurodov, Isomiddin; Khalifaev, Davlat; Safarzoda, Ramazon; Sobeh, Mansour; Wink, Michael (Pharmaceutical chemistry journal, 2020)
The present study was aimed at investigation of the chemical composition, antioxidant and cytotoxic activities of topinambur Helianthus tuberosus L. extracts for its further application in medicine. Crude methanol extract from the tubers of H. tuberosus L. cultivated in Tajikistan, was analyzed by liquid chromatography-mass spectrometry (LC-MS/MS) method. Chlorogenic and 1,5-dicaffeoylquinic acids were identified as major components of the tuber methanol extract by NMR and peak matching in LC-MS/MS chromatogram with defined standards. Total phenolic and flavonoid contents of the methanol and aqueous extracts were determined using Folin - Ciocalteu and aluminum colorimetric methods, respectively. The methanol extract showed substantial phenolic and flavonoid contents in comparison to the aqueous extract. Total phenolic and flavonoid contents of 67.12 ± 1.2 mg caffeic acid equivalent and 3.53 ± 0.1 mg quercetin equivalent per gram of the methanol extract were determined. Their antioxidant capacity was evaluated using DPPH, ABTS, and FRAP assays. Half -inhibitory (IC50) values of the methanol extract were 13.61 ± 0.1 μg/mL for DPPH and 30.23 ± 0.4 μg/mL for ABTS test, respectively. The FRAP value of the methanol extract and positive control were 850.24 ± 14 and 2380 ± 46 mM FeSO4/mg extract, respectively. The aqueous extract exhibited low antioxidant activity. In addition, cytotoxicity of the methanol extracts was evaluated using MTT assay on CCRF-CEM and P-gp overexpressing CEM/ADR5000 cancer cell lines. The methanol extract showed a rather weak activity with IC50 values 265.0 μg/mL for CCRF-CEM and 345.9 μg/mL for CEM/ADR5000. As CEM/ADR5000 cells overexpress the ABC transporter P-gp, this result indicated that the extract apparently contained substances which affect P-gp, which need further investigations. In conclusion, methanol extract of H. tuberosus is rich with chlorogenic and 1,5-dicaffeoylquinic acid and exhibits strong antioxidant activity and weak cytotoxicity.